Proposal for a privacy policy manager as architecture for a new privacy-enhancing platform - Haruo Takasaki; Toru Nakamura; Shinsaku Kiyomoto (International Telecommunications Society (ITS), 2017)
Refinement of the legal framework that balancesthe protection and usage of personal data in online and offline services has been discussed globally. On the other hand, because of information asymmetry between users and service providers and bounded rationality of users, the existing notice-and-consent mechanism (Solove's privacy self-management model) has proven inadequate in itseffectiveness. This research contributes to solvingthe abovementioned issues usinga complementary technical system(named Privacy Policy Manager). The Privacy Policy Manager creates users'privacy policies based on theirpreferences and supports them incontrollingdata disclosure and data usage in accordance with thesepolicies.
Keywords: 330; Privacy; Personal Data; Data Protection; PDS; Privacy by Design